Melting-stretching preparation method of aramid pulp embedded PVDF hollow fiber microfiltration membrane

By introducing aramid pulp and soluble polymers in the preparation of PVDF hollow fiber membranes, and using melt spinning and post-stretching processes, the problems of insufficient water flux and mechanical properties of the membrane in the prior art are solved, and green and environmentally friendly High performance membrane preparation.

CN119425401AActive Publication Date: 2025-02-14SHANGHAI UNIV OF ENG SCI
View PDF 17 Cites 0 Cited by

Patent Information

Application Number
CN202411647731.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-14
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

The existing PVDF hollow fiber membranes use organic solvents and diluents during the preparation process, resulting in wastewater contamination, and the water flux and mechanical properties of the membrane are poor.

Method used

The melt-stretching preparation method of aramid pulp embedded PVDF hollow fiber microfiltration membrane is used to mix PVDF, soluble inorganic substances, soluble polymers and aramid pulp through a high-speed mixer to perform melt-spinning and post-stretching. Treatment to form a membrane with a multi-porous structure.

Benefits of technology

A green filmmaking process without using organic solvents is realized, which improves the pure water flux and mechanical strength of the film, ensures good physical and chemical properties of the film, and reduces environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119425401A_ABST
    Figure CN119425401A_ABST
Patent Text Reader

Abstract

The invention discloses a melting-stretching preparation method of an aramid pulp embedded PVDF (polyvinylidene fluoride) hollow fiber microfiltration membrane, which comprises the following steps: taking polyvinylidene fluoride (PVDF) as a matrix phase, using two soluble polymers and insoluble polymers as composite pore-forming agents, doping aramid pulp as a dispersed phase, and taking titanium dioxide as an additive, thereby preparing the aramid pulp embedded PVDF hollow fiber microfiltration membrane. Preparing a primary hollow fiber membrane by a melt spinning method; and performing post-treatment on the primary membrane, and soaking the primary membrane in clear water to dissolve out the composite pore-forming agent to form dissolution holes, thereby forming a stable multi-pore structure. According to the method, no organic solvent or etching liquid is added, the hollow fiber membrane is obtained by using the composite pore-forming agent and the aramid fiber pulp in a matched mode and then adopting a stretching technology, discharge of organic wastewater in the PVDF spinning membrane manufacturing process is avoided, the mechanical property of the hollow fiber membrane is good, and the pure water flux is relatively high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hollow fiber membranes, and in particular relates to a melt-stretching preparation method of an aramid pulp embedded PVDF hollow fiber microfiltration membrane. Background Art

[0002] Membrane separation technology has been widely used in the field of water treatment due to its green, environmentally friendly and efficient characteristics. PVDF has become the most popular membrane material due to its excellent mechanical strength, antioxidant and chemical corrosion resistance, and is widely used to prepare microfiltration and ultrafiltration membranes. However, PVDF can be dissolved in a variety of organic solvents at room temperature or lower temperatures, so non-solvent induced phase separation (NIPS) or thermally induced phase separation (TIPS) methods are usually used to prepare PVDF hollow fiber membranes. Various solvents or diluents are usually used in the preparation process, such as N, N-dimethylformamide (DMF), N, N-dimethylacetamide (DMAC), dioctyl phthalate (DOP), etc., which will produce a large amount of industrial wastewater that is difficult to recycle, resulting in a waste of water resources. At present, some researchers are trying to use low-toxic or even non-toxic organic solvents and diluents to achieve a green membrane process. However, these methods can only reduce the harm of wastewater to the human body and the environment during the preparation of separation membranes, and cannot completely solve the problem of wastewater generation and recycling.

[0003] Therefore, in this context, it is crucial to design a green membrane-making process. Compared with the NIPS and TIPS processes, the melt spinning and stretching (MS-S) technology is a relatively green membrane preparation process. The melt spinning-stretching method is to extrude the polymer melt through a spinneret under high-temperature shearing, solidify it after cooling, and then separate the lamellae structure arranged parallel to the extrusion direction in the primary hollow fiber membrane through post-stretching to form pores. However, the porosity and pore structure connectivity of the membrane obtained by this method are lower than those of the membrane prepared by the NIPS method, which is manifested as a lower water flux of the hollow fiber porous membrane, and its performance needs to be improved.

[0004] In response to the above problems, researchers are committed to finding a method for preparing a green, pollution-free, stable, and relatively high pure water flux PVDF hollow fiber membrane, which can reduce or even eliminate the pollution problem in the membrane preparation process while ensuring the good physical and chemical properties of the membrane. Summary of the invention

[0005] One object of the present invention is to provide a melt-stretching preparation method for aramid pulp embedded PVDF hollow fiber microfiltration membrane to solve the problem that the existing membrane making method cannot take into account both good water flux and high strength of the membrane.

[0006] Another object of the present invention is to provide a PVDF hollow fiber membrane prepared by the above method with relatively high pure water flux, so as to solve the problems of poor mechanical properties, small membrane flux and instability of the hollow fiber membrane prepared by the prior art.

[0007] To this end, the present invention adopts the following technical solutions:

[0008] A melt-stretching preparation method of an aramid pulp embedded PVDF hollow fiber microfiltration membrane comprises the following steps:

[0009] (1) Material mixing: PVDF (polyvinylidene fluoride) is used as a matrix phase, a soluble inorganic substance and two soluble polymers are used as composite pore-forming agents, aramid pulp is used as a dispersed phase, and titanium dioxide is used as an additive. A high-speed mixer is used to mix them uniformly in proportion to obtain a spinning raw material and a uniformly mixed material.

[0010] (2) melt spinning: the material obtained in step (1) is put into a twin-screw extruder for melt granulation, and after blending, it is heated at high temperature by a twin-screw extruder, and the spinning melt is quantitatively extruded through a hollow spinneret assembly, and air is introduced into the hollow spinneret assembly. The spinning melt is solidified in an air bath to obtain a primary hollow fiber membrane;

[0011] (3) Post-treatment: The nascent hollow fiber membrane is air-dried and then immersed in 70°C water for 24 hours to dissolve the soluble inorganic matter and two soluble polymers. The membrane is dried in an oven and preheated for 2 to 4 hours. The membrane is then heat-stretched at a certain rate to a certain multiple to obtain a stretched hollow fiber membrane. The preheating temperature and the heat-stretching temperature are the same to obtain a PVDF hollow fiber membrane with a relatively high pure water flux.

[0012] Preferably, in step (1), the soluble inorganic substance is at least one of sodium chloride, calcium chloride or magnesium chloride.

[0013] Preferably, in step (1), the soluble polymer is at least two of polyethylene oxide, polyethylene glycol, polyacrylamide or polyvinyl pyrrolidone.

[0014] Preferably, in step (1), the aramid pulp fiber has a diameter of 7 to 15 μm and a length of 0.5 to 2.5 mm.

[0015] Preferably, in step (1), the titanium dioxide is in the form of rods of TiO2 with a length of 130 to 150 nm and a diameter of 20 to 30 nm.

[0016] Preferably, the mass fraction of the PVDF matrix phase is 40-65wt%, the mass fraction of the soluble inorganic matter is 15-30wt%, the mass fraction of the soluble polymer is 15-30wt%, the mass fraction of the aramid pulp is 0.5-2wt%, the mass fraction of titanium dioxide is 0-3wt%, and the sum of the mass fractions of each component is 100wt%.

[0017] Preferably, in step (2), the melt temperature is 220-250°C.

[0018] Preferably, the rate of the heat stretching in step (3) is 10 to 20 mm / min.

[0019] Preferably, the thermal stretching ratio in step (3) is 100-200%.

[0020] Preferably, the preheating temperature and the heat stretching temperature in step (3) are 90 to 120°C.

[0021] In step (3), the hollow fiber membrane after stretching has a multiple pore structure, wherein circular micropores are formed by the dissolution of soluble inorganic substances, vertical continuous macropores are macropores formed by two soluble organic substances wrapping inorganic substances during the melting process, and vertical continuous micropores are formed by the dissolution of two soluble organic substances. In addition, due to the addition of aramid pulp, interfacial pores can be formed along the stretching direction during the hot stretching process.

[0022] The above preparation method is used to prepare an aramid pulp embedded PVDF hollow fiber microfiltration membrane, which has a multiple pore structure, including circular micropores formed by the dissolution of soluble inorganic substances, vertical continuous macropores formed by two soluble organic substances enveloping inorganic substances during the melting process, and vertical continuous micropores formed by the dissolution of two soluble organic substances. In addition, due to the addition of aramid pulp, interfacial pores can be formed along the stretching direction during the thermal stretching process. The pure water flux of the membrane is 500-3000L / m 2 ·h, the average pore size of the multi-pore structure ranges from 0.4 to 2 μm, the fracture strength of the membrane is 25 to 80 MPa, the water contact angle of the membrane is less than 100°, and the SiO2 retention rate is greater than 80%.

[0023] Beneficial effects of the present invention: The present invention adopts a combination of melt spinning and post-stretching to prepare a PVDF hollow fiber membrane doped with aramid pulp and having multiple pores with relatively high pure water flux. From the perspective of the membrane forming process, the present invention dopes aramid pulp, selects soluble organic matter and two soluble polymers as composite pore-forming agents, does not add any organic solvents and etching liquids during the preparation process, adopts dissolution pore-forming and post-stretching processes to obtain a hollow fiber membrane, and avoids the discharge of organic wastewater during the PVDF spinning and membrane-making process. The method is stable, feasible, green and environmentally friendly, and does not pollute the environment.

[0024] From the perspective of the structure of the prepared hollow fiber membrane, the present invention adopts a method of using a composite pore-forming agent and doping aramid pulp, so that after the composite pore-forming agent is dissolved, a variety of uniform macropores are left on the fiber membrane. The combination of the composite pore-forming agent provides favorable conditions for the subsequent multiple pore formation. In the post-stretching process, aramid pulp is used. Since a large number of fibrillated fibers of aramid pulp are distributed and embedded in the PVDF matrix, the size of the PVDF interface pores can be increased along the stretching direction during the stretching process, which is significantly different from the traditional particle pore-forming method, and the continuity between the membrane pores and the membrane pore density per unit area are enhanced. At the same time, due to the rigidity of aramid pulp, the strength of the hollow fiber membrane is guaranteed. The addition of rod-shaped TiO2 promotes the formation of β-crystals in the PVDF hollow fiber membrane, enhances elasticity, and prolongs the service life of the membrane.

[0025] The pore size range of the multi-pore structure of the aramid pulp embedded PVDF hollow fiber microfiltration membrane of the present invention is 0.4-2 μm, and the pure water flux of the high-strength and high-flux PVDF hollow fiber membrane doped with aramid pulp is 500-3000 L / m 2 ·h, breaking strength is 25-80MPa, water contact angle is less than 100°, SiO2 retention rate is >80%. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the following briefly introduces the drawings required for describing the embodiment, wherein:

[0027] Figure 1 This is a scanning electron microscope image of the outer surface of the PVDF hollow fiber membrane prepared in Example 1.

[0028] Figure 2 This is a scanning electron microscope image of the cross section of the PVDF hollow fiber membrane prepared in Example 1. DETAILED DESCRIPTION

[0029] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with specific embodiments.

[0030] Embodiment 1:

[0031] A melt-stretching preparation method of an aramid pulp embedded PVDF hollow fiber microfiltration membrane comprises the following steps:

[0032] (1) Material mixing: PVDF is used as a matrix phase, a soluble inorganic substance (MgCl2) and two soluble polymers (PAM, PVP) are used as composite pore-forming agents, and aramid pulp is used as a dispersed phase. According to the mass fraction of 56.5wt% of PVDF (Solvay 6010), 20.0wt% of MgCl2, 13.0wt% of PAM (polyacrylamide, average molecular weight 1 million), 10.0wt% of PVP (polyvinyl pyrrolidone, average molecular weight 58000) and 0.5wt% of aramid pulp 1F538, a high-speed mixer is used to mix them uniformly in proportion to obtain a spinning raw material and a uniformly mixed material;

[0033] (2) Melt spinning: The material obtained in step (1) is put into a twin-screw extruder (SHJ-20, Jiangsu Qijie Machinery Co., Ltd.) for melt granulation. After blending, the material is heated at high temperature by a twin-screw extruder, and a spinning melt (diameter of about 2.6 mm) is quantitatively extruded through a hollow spinneret assembly (spinneret diameter 2.85 mm). The temperature of each zone of the twin-screw extruder is: 160° C. for zone 1, 180° C. for zone 2, 220° C. for zone 3, 220° C. for zone 4, 230° C. for zone 5, 230° C. for zone 6, 230° C. for zone 7, 230° C. for zone 8, and 230° C. for zone 9; air is introduced into the hollow spinneret assembly, and the spinning melt is solidified in an air bath to obtain a primary hollow fiber membrane (membrane thickness 0.35 mm);

[0034] (3) Post-treatment: After the nascent hollow fiber membrane is air-dried, it is immersed in 70°C water for 24 hours to dissolve the soluble inorganic matter and the two soluble polymers. It is then dried in an oven at 90°C and preheated for 2 to 4 hours. It is then stretched at 110°C to an elongation of 100% (based on the length of the nascent hollow fiber membrane. Stretching to twice the length of the nascent hollow fiber membrane means an elongation of 100%) at a stretching rate of 10 mm / mim to obtain a stretched hollow fiber membrane, i.e., a PVDF hollow fiber membrane with a relatively high pure water flux.

[0035] The pure water flux of the obtained PVDF hollow fiber membrane was tested at 0.1 MPa, and the flux was measured to be 1850 L / m 2 ·h; the pore size of the hollow fiber membrane was measured to be 1.03μm; the fracture strength of the PVDF hollow fiber membrane was tested to be 69.7MPa at a clamping distance of 10cm and a tensile speed of 10mm / min; the water contact angle of the surface of the PVDF hollow fiber membrane was measured to be 98.1° using a contact angle meter; the PVDF hollow fiber membrane was tested for SiO2 (0.1g·L-1 ,800nm) suspension had a retention rate of 98.8%.

[0036] The outer surface of the prepared PVDF hollow fiber membrane was scanned by electron microscope, and the results were as follows: Figure 1 As shown, from Figure 1 It can be seen that the PVDF hollow fiber membrane prepared in this embodiment has a multiple pore structure, which includes circular micropores formed by the dissolution of soluble inorganic substances, vertical continuous macropores formed by two soluble organic substances wrapping inorganic substances during the melting process, and vertical continuous micropores formed by the dissolution of two soluble organic substances. In addition, due to the addition of aramid pulp, interfacial pores can be formed along the stretching direction during the hot stretching process.

[0037] The cross section of the prepared PVDF hollow fiber membrane was scanned by electron microscope, and the results were as follows: Figure 2 As shown, from Figure 2 It can be seen that the pore structure of the cross section of the hollow fiber membrane with aramid pulp added. Since the compatibility between PVDF and aramid pulp is poor, this is because the PPTA molecular chain is rigid, not easy to bend and fold, and the molecular contact area between it and the flexible molecular chain of PVDF is small, and it is not easy to form intermolecular forces, so the compatibility is not high. In addition, aramid fiber does not melt during processing, which allows the fluff structure on its surface to be completely retained in the primary membrane. The rich fluff on the surface is conducive to enhancing the continuity between the membrane pores, and the highly fibrillated characteristics of aramid pulp make its surface contain rich fluff, so the aramid pulp fiber is embedded in the PVDF matrix, forming many protruding flocculent structures.

[0038] Embodiment 2:

[0039] A melt-stretching preparation method of an aramid pulp embedded PVDF hollow fiber microfiltration membrane comprises the following steps:

[0040] (1) Material mixing: PVDF is used as a matrix phase, a soluble inorganic substance and two soluble polymers are used as composite pore-forming agents, and aramid pulp is used as a dispersed phase. According to the mass fraction of 55.5wt% of PVDF (Solvay 6010), 20.0wt% of CaCl2, 13.5wt% of PEO (polyethylene oxide, average molecular weight 1000000), 10.0wt% of PEG (polyethylene glycol, average molecular weight 20000), and 1.0wt% of aramid pulp 1F1710, a high-speed mixer is used to mix them uniformly in proportion to obtain a spinning raw material and a uniformly mixed material;

[0041] (2) Melt spinning: The material obtained in step (1) is put into a twin-screw extruder (SHJ-20, Jiangsu Qijie Machinery Co., Ltd.) for melt granulation, and then heated at high temperature by a twin screw after blending, and quantitatively extruded into a spinning melt (with a diameter of 2.6 mm) through a hollow spinneret assembly (spinneret diameter 2.85 mm), wherein the temperature of each zone of the twin screw is: 160° C. for zone 1, 180° C. for zone 2, 220° C. for zone 3, 220° C. for zone 4, 230° C. for zone 5, 230° C. for zone 6, 230° C. for zone 7, 230° C. for zone 8, and 230° C. for zone 9; air is introduced into the hollow spinneret assembly, and the spinning melt is solidified in an air bath to obtain a primary hollow fiber membrane (with a membrane thickness of 0.34 mm);

[0042] (3) Post-treatment: The nascent hollow fiber membrane is air-dried and then immersed in 70°C water for 24 hours to dissolve the soluble inorganic matter and two soluble polymers, dried in an oven at 90°C and preheated for 2N4h, and then hot-stretched at 100°C to an elongation of 150% (based on the length of the nascent hollow fiber membrane, stretched to 2.5 times the length of the nascent hollow fiber membrane, i.e., an elongation of 150%), with a stretching rate of 10 mm / min, to obtain a stretched hollow fiber membrane, thereby obtaining a PVDF hollow fiber membrane with a relatively high pure water flux.

[0043] The pure water flux of the obtained PVDF hollow fiber membrane was tested at 0.1 MPa, and the flux was measured to be 2445 L / m 2 ·h; the pore size of the hollow fiber membrane was measured to be 1.14μm; the fracture strength of the PVDF hollow fiber membrane was tested to be 72.4MPa at a clamping distance of 10cm and a tensile speed of 10mm / min; the water contact angle of the surface of the PVDF hollow fiber membrane was measured to be 92.2° using a contact angle meter; the PVDF hollow fiber membrane was tested for SiO2 (0.1g·L -1 , 800nm) suspension had a retention rate of 85.3%.

[0044] Compared with Example 1, Example 2 increases the content of aramid pulp to 1.0wt%. As the content of aramid pulp increases, the membrane pores on the cross-section surface increase and the pore structure increases; in addition, the increase in the content of aramid pulp promotes the increase of the surface extended flocculent structure and the formation of interface pores. Therefore, the pore size of the membrane increases from 1.03μm to 1.14μm, and the flux also increases from 1850L / m 2 ·h increased to 2445L / m 2 ·h. At the same time, as the aramid pulp content increased, the breaking strength of the hollow fiber membrane was improved from 69.7MPa to 72.4MPa. Compared with Example 1, the water contact angle of the membrane decreased. When the aramid pulp content was 1.0wt%, the SiO2 retention rate was 85.3%.

[0045] Embodiment 3:

[0046] A melt-stretching preparation method of an aramid pulp embedded PVDF hollow fiber microfiltration membrane comprises the following steps:

[0047] (1) Material mixing: PVDF is used as a matrix phase, a soluble inorganic substance and two soluble polymers are used as composite pore-forming agents, and aramid pulp is used as a dispersed phase. According to the mass fraction of 54.5wt% of PVDF (Solvay 6010), 25.0wt% of NaCl, 11.0wt% of PAM 1000000, 8.0wt% of PVP 58000, and 1.5wt% of aramid pulp 1F538, a high-speed mixer is used to mix them uniformly in proportion to obtain a spinning raw material, thereby obtaining a uniformly mixed material;

[0048] (2) Melt spinning: The material obtained in step (1) is put into a twin-screw extruder (SHJ-20, Jiangsu Qijie Machinery Co., Ltd.) for melt granulation, and then heated at high temperature by a twin screw after blending, and quantitatively extruded into a spinning melt (with a diameter of 2.6 mm) through a hollow spinneret assembly (spinneret diameter 2.85 mm), wherein the temperature of each zone of the twin screw is: 160° C. for zone 1, 180° C. for zone 2, 220° C. for zone 3, 220° C. for zone 4, 230° C. for zone 5, 230° C. for zone 6, 230° C. for zone 7, 230° C. for zone 8, and 230° C. for zone 9; air is introduced into the hollow spinneret assembly, and the spinning melt is solidified in an air bath to obtain a primary hollow fiber membrane (with a membrane thickness of 0.36 mm);

[0049] (3) Post-treatment: After the nascent hollow fiber membrane is air-dried, it is immersed in 70°C water for 24 hours to dissolve the soluble inorganic matter and two soluble polymers, dried in an oven at 90°C and preheated for 2 to 4 hours, and then hot-stretched at 110°C to an elongation of 100% (based on the length of the nascent hollow fiber membrane) and a stretching rate of 10 mm / mim to obtain a stretched hollow fiber membrane, thereby obtaining a PVDF hollow fiber membrane with a relatively high pure water flux.

[0050] The pure water flux of the obtained PVDF hollow fiber membrane was tested at 0.1 MPa, and the flux was measured to be 2730 L / m 2 ·h; the pore size of the hollow fiber membrane was measured to be 1.21μm; the fracture strength of the PVDF hollow fiber membrane was tested to be 75.7MPa at a clamping distance of 10cm and a tensile speed of 10mm / min; the water contact angle of the surface of the PVDF hollow fiber membrane was measured to be 88.3° using a contact angle meter; the PVDF hollow fiber membrane was tested for SiO2 (0.1g·L -1, 800nm) suspension retention rate was 95.2%.

[0051] Compared with Example 2, Example 3 increases the content of aramid pulp to 1.5wt%. As the content of aramid pulp increases, the membrane pores on the cross-section surface increase and the pore structure increases; in addition, the increase in the content of aramid pulp promotes the increase of the surface extended flocculent structure and the formation of interface pores. Therefore, the pore size of the membrane increases from 1.14μm to 1.21μm, and the flux also increases from 2445L / m 2 ·h increased to 2730L / m 2 ·h. At the same time, as the aramid pulp content increased, the breaking strength of the hollow fiber membrane was improved from 72.4MPa to 75.7MPa. Compared with Example 2, the water contact angle of the membrane decreased from 92.2° to 88.3°, and the SiO2 retention rate increased from 85.3% to 95.2%.

[0052] Embodiment 4:

[0053] A melt-stretching preparation method of an aramid pulp embedded PVDF hollow fiber microfiltration membrane comprises the following steps:

[0054] (1) Material mixing: PVDF is used as a matrix phase, soluble inorganic substances and two soluble polymers are used as composite pore-forming agents, aramid pulp is used as a dispersed phase, and titanium dioxide is used as an additive. According to the mass fraction of 54.5wt% of PVDF (Solvay 6010), 23.0wt% of CaCl2, 11.0wt% of PEO 1000000, 8.0wt% of PEG 20000, 1.5wt% of aramid pulp 1F1710 and 2.0wt% of rod-shaped TiO2 (length 130-150nm, diameter 20-30nm), a high-speed mixer is used to mix them uniformly in proportion to obtain a spinning raw material and a uniformly mixed material;

[0055] (2) Melt spinning: The material obtained in step (1) is put into a twin-screw extruder (SHJ-20, Jiangsu Qijie Machinery Co., Ltd.) for melt granulation. After blending, the material is heated at high temperature by a twin-screw extruder, and a spinning melt (diameter of 2.6 mm) is quantitatively extruded through a hollow spinneret assembly (spinneret diameter of 2.85 mm). The temperature of each zone of the twin-screw extruder is: 160° C. for zone 1, 180° C. for zone 2, 220° C. for zone 3, 220° C. for zone 4, 230° C. for zone 5, 230° C. for zone 6, 230° C. for zone 7, 230° C. for zone 8, and 230° C. for zone 9; air is introduced into the hollow spinneret assembly, and the spun body is solidified in an air bath to obtain a primary hollow fiber membrane (membrane thickness of 0.35 mm);

[0056] (3) Post-treatment: After the nascent hollow fiber membrane is air-dried, it is immersed in 70°C water for 24 hours to dissolve the soluble inorganic matter and two soluble polymers, dried in an oven at 90°C and preheated for 2N4h, and then hot-stretched at 110°C to an elongation of 100% (based on the length of the nascent hollow fiber membrane) and a stretching rate of 10 mm / mim to obtain a stretched hollow fiber membrane, thereby obtaining a PVDF hollow fiber membrane with a relatively high pure water flux.

[0057] The pure water flux of the obtained PVDF hollow fiber membrane was tested at 0.1 MPa, and the measured flux was 2935 L / m 2 ·h; the pore size of the hollow fiber membrane was measured to be 1.35μm; the fracture strength of the PVDF hollow fiber membrane was tested to be 78.8M Pa at a clamping distance of 10cm and a tensile speed of 10mm / min; the water contact angle of the surface of the PVDF hollow fiber membrane was measured to be 87.2° using a contact angle meter; the PVDF hollow fiber membrane was tested for SiO2 (0.1g·L -1 , 800nm) suspension had a retention rate of 97.8%.

[0058] Compared with Example 3, Example 4 adds 2.0wt% of rod-shaped TiO2. The pores formed by the rod-shaped TiO2 are vertical pores, which are consistent with the stretching direction, so the pore size will increase. The pore size of the membrane increases from 1.21μm to 1.35μm, and the flux also increases from 2730L / m 2 ·h increased to 2935L / m 2 h, the fracture strength of the hollow fiber membrane increased from 75.7 MPa to 78.8 MPa. Compared with Example 3, the water contact angle of the membrane decreased from 88.3° to 87.2°, and the SiO2 retention rate increased from 95.2% to 97.8%.

[0059] Embodiment 5:

[0060] A melt-stretching preparation method of an aramid pulp embedded PVDF hollow fiber microfiltration membrane comprises the following steps:

[0061] (1) Material mixing: PVDF is used as a matrix phase, a soluble inorganic substance and two soluble polymers are used as composite pore-forming agents, aramid pulp is used as a dispersed phase, and titanium dioxide is used as an additive. According to the mass fraction of 54.5wt% of PVDF (Solvay 6010), 22.0wt% of MgCl2, 11.0wt% of PEO 1000000, 8.0wt% of PEG 20000, 1.5wt% of aramid pulp 1F1710 and 3.0wt% of rod-shaped TiO2, a high-speed mixer is used to mix them uniformly in proportion to obtain a spinning raw material, thereby obtaining a uniformly mixed material;

[0062] (2) Melt spinning: The material obtained in step (1) is put into a twin-screw extruder (SHJ-20, Jiangsu Qijie Machinery Co., Ltd.) for melt granulation. After blending, the material is heated at high temperature by a twin-screw extruder, and a spinning melt (diameter of 2.6 mm) is quantitatively extruded through a hollow spinneret assembly (spinneret diameter of 2.85 mm). The temperature of each zone of the twin-screw extruder is: 160° C. for zone 1, 180° C. for zone 2, 220° C. for zone 3, 220° C. for zone 4, 230° C. for zone 5, 230° C. for zone 6, 230° C. for zone 7, 230° C. for zone 8, and 230° C. for zone 9; air is introduced into the hollow spinneret assembly, and the spun body is solidified in an air bath to obtain a primary hollow fiber membrane (membrane thickness of 0.35 mm);

[0063] (3) Post-treatment: After the nascent hollow fiber membrane is air-dried, it is immersed in 70°C water for 24 hours to dissolve the soluble inorganic matter and two soluble polymers, dried in an oven at 90°C and preheated for 2 to 4 hours, and then hot-stretched at 100°C to an elongation of 150% (based on the length of the nascent hollow fiber membrane) and a stretching rate of 10 mm / mim to obtain a stretched hollow fiber membrane, thereby obtaining a PVDF hollow fiber membrane with a relatively high pure water flux.

[0064] The pure water flux of the obtained PVDF hollow fiber membrane was tested at 0.1 MPa, and the flux was measured to be 1920 L / m 2 ·h; the pore size of the hollow fiber membrane was measured to be 1.05μm; the fracture strength of the PVDF hollow fiber membrane was tested to be 79.5MPa at a clamping distance of 10cm and a tensile speed of 10mm / min; the water contact angle of the surface of the PVDF hollow fiber membrane was measured to be 86.6° using a contact angle meter; the PVDF hollow fiber membrane was tested for SiO2 (0.1g·L -1 , 800nm) suspension retention rate was 98.3%.

[0065] Compared with Example 4, Example 5 added 3.0wt% of rod-shaped TiO2, the pore size of the membrane was reduced from 1.35μm to 1.05μm, and the flux was increased from 2935L / m 2 ·h reduced to 1920L / m 2 h, the fracture strength of the hollow fiber membrane increased from 78.8MPa to 79.5MPa, the water contact angle of the membrane decreased from 87.2° to 86.6°, and the SiO2 retention rate increased from 97.8% to 98.3%. Excessive content of rod-shaped TiO2 is not conducive to the pure water flux of the membrane.

[0066] Comparative Example 1:

[0067] The preparation method is the same as that in Example 1, except that the material ratio in step (1) is: 54.5wt% PVDF6010, 18.0wt% MgCl2, 12.5wt% PAM1000000, 10.0wt% PVP58000 and 5.0wt% aramid pulp 1F538.

[0068] The pure water flux of the obtained PVDF hollow fiber membrane was tested at 0.1 MPa, and the flux was measured to be 975 L / m 2 ·h; the pore size of the hollow fiber membrane was measured to be 0.52μm; the fracture strength of the PVDF hollow fiber membrane was tested to be 100.6MPa at a clamping distance of 10cm and a tensile speed of 10mm / min; the water contact angle of the surface of the PVDF hollow fiber membrane was measured to be 70.5° using a contact angle meter; the PVDF hollow fiber membrane was tested for SiO2 (0.1g·L -1 ,800nm) suspension retention rate was 70.8%.

[0069] Compared with Example 1, adding 5.0wt% of aramid pulp 1F538, the pore size of the membrane increased from 1.03μm to 1.05μm, and the flux also increased from 1850L / m 2 ·h increased to 1920L / m 2 h, the breaking strength of the membrane increased from 69.7MPa to 74.3MPa. The water contact angle of the membrane decreased from 98.1° to 70.5°, and the SiO2 retention rate decreased from 98.8% to 70.8%. This shows that adding excessive aramid pulp will not significantly improve the permeability of the membrane, but will significantly reduce the retention performance of the membrane.

[0070] Comparative Example 2:

[0071] The preparation method is the same as that in Example 2, except that the material ratio in step (1) is: 55.5wt% PVDF (Solvay 6010), 20.0wt% CaCl2, 13.5wt% PEO1000000, 10.0wt% PEG20000, and 1.0wt% aramid staple fiber 1414.

[0072] The pure water flux of the obtained PVDF hollow fiber membrane was tested at 0.1 MPa, and the flux was measured to be 830 L / m 2·h; the pore size of the hollow fiber membrane was measured to be 0.46μm; the fracture strength of the PVDF hollow fiber membrane was 53.5MPa when the clamping distance was 10cm and the tensile speed was 10mm / min; the water contact angle of the surface of the PVDF hollow fiber membrane was measured by a contact angle meter and was 104.9°; the PVDF hollow fiber membrane was tested for SiO2 (0.1g·L -1 , 800nm) suspension had a retention rate of 73.2%.

[0073] Comparative Example 2, in which aramid staple fibers were added, the pore size of the membrane was reduced from 1.14 μm to 0.46 μm, and the flux was also reduced from 2445 L / m 2 ·h reduced to 830L / m 2 h, the fracture strength of the hollow fiber membrane decreased from 72.4MPa to 53.5MPa, the water contact angle of the membrane increased from 92.2° to 104.9°, and the SiO2 retention rate decreased from 85.3% to 73.2%. It can be seen that aramid pulp is better than aramid staple fiber, and aramid pulp can improve the mechanical properties, permeability and retention performance of the membrane.

[0074] Comparative Example 3:

[0075] The same as Example 4, except that the proportion of rod-shaped TiO2 in the material of step (1) of Example 4 was replaced with 5.0 wt%.

[0076] The pure water flux of the obtained PVDF hollow fiber membrane was tested at 0.1 MPa, and the flux was measured to be 1570 L / m 2 ·h; the pore size of the hollow fiber membrane was measured to be 0.85μm; the fracture strength of the PVDF hollow fiber membrane was tested to be 82.3MPa at a clamping distance of 10cm and a tensile speed of 10mm / min; the water contact angle of the surface of the PVDF hollow fiber membrane was measured to be 80.5° using a contact angle meter; the PVDF hollow fiber membrane was tested for SiO2 (0.1g·L -1 ,800nm) suspension had a retention rate of 99.4%.

[0077] Comparative Example 4, the proportion of rod-shaped TiO2 increased to 5.0wt%, the pore size increased from 1.35μm to 1.63μm, and the flux also increased from 2935L / m 2 ·h reduced to 1570L / m 2h, the fracture strength increased from 79.8MPa to 82.3MPa, the water contact angle of the membrane decreased from 87.2° to 80.5°, and the SiO2 retention rate increased from 97.8% to 99.4%. Comprehensively speaking, the content of rod-shaped TiO2 is not as high as possible. Although the fracture strength and SiO2 retention rate of control example 3 are improved, the flux is greatly reduced. Considering the water treatment efficiency of the membrane, excessive rod-shaped TiO2 should not be added.

[0078] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A melt-stretching preparation method of aramid pulp embedded PVDF hollow fiber microfiltration membrane, characterized in that: It consists of the following steps: (1) Material mixing: PVDF is used as a matrix phase, soluble inorganic matter and soluble polymer are used as composite pore-forming agents, and aramid pulp is used as a dispersed phase, and the mixture is uniformly mixed to obtain a uniformly mixed material; the mass fraction of the PVDF matrix phase is 40-65wt%, the mass fraction of the soluble inorganic matter is 15-30wt%, the mass fraction of the soluble polymer is 15-30wt%, the mass fraction of the aramid pulp is 0.5-2wt%, and the sum of the mass fractions of the components is 100wt%; (2) melt spinning: the material obtained in step (1) is put into a twin-screw extruder, and after blending, it is heated at high temperature by a twin-screw extruder to be melt-granulated, and the spinning melt is quantitatively extruded through a hollow spinneret assembly; air is introduced into the hollow spinneret assembly, and the spinning melt is solidified in an air bath to obtain a primary hollow fiber membrane; (3) Post-treatment: The nascent hollow fiber membrane is air-dried, then soaked in hot water, dried and preheated in an oven, and then heat-stretched to obtain an aramid pulp embedded PVDF hollow fiber microfiltration membrane.

2. The preparation method according to claim 1, characterized in that: In step (1), the soluble inorganic substance is at least one of sodium chloride, calcium chloride or magnesium chloride.

3. The preparation method according to claim 1 or 2, characterized in that: In step (1), the soluble polymer is at least two of polyethylene oxide, polyethylene glycol, polyacrylamide or polyvinyl pyrrolidone.

4. The preparation method according to claim 1 or 2, characterized in that: In step (1), the fiber diameter of the aramid pulp is 7 to 15 μm, and the fiber length is 0.5 to 2.5 mm.

5. The preparation method according to claim 1 or 2, characterized in that: Step (1) also includes adding titanium dioxide as an additive to the material; the titanium dioxide is rod-shaped titanium dioxide, and the average length of the rod-shaped titanium dioxide is 130 to 150 nm and the average diameter is 20 to 30 nm.

6. The preparation method according to claim 5, characterized in that: The mass fraction of titanium dioxide is less than or equal to 3 wt%.

7. The preparation method according to claim 1 or 2, characterized in that: In step (2), the spinning melt temperature is 220-250°C.

8. The preparation method according to claim 1 or 2, characterized in that: In step (3), the heat stretching rate is 10 to 20 mm / min.

9. The preparation method according to claim 1 or 2, characterized in that: In step (3), the length of the aramid pulp embedded PVDF hollow fiber microfiltration membrane obtained after the heat stretching is increased by 100-200% compared with the initial hollow fiber membrane.

10. The preparation method according to claim 1 or 2, characterized in that: In step (3), the preheating temperature is the same as the heat stretching temperature, which is 90 to 120°C.

Citation Information

Patent Citations

  • Hollow fiber ultrafilter membrane and its preparation method

    CN102489170A

  • Aromatic polyamide hollow fiber membrane, preparation method and application

    CN106693729A

  • Chitosan / graphite phase carbon nitride / titanium dioxide nanofiber membrane as well as preparation method and application thereof

    CN111250056A

  • Preparation method of electromagnetic shielding composite fiber membrane

    CN112709012A

  • Solvent-free polyvinylidene fluoride hollow fiber membrane and preparation method thereof

    CN114191995A